1993
DOI: 10.1002/1098-108x(199307)14:1<111::aid-eat2260140115>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Body size and shape characteristics of personal (“in search of”) ads

Abstract: This study investigated sociocultural norms for height, weight, and body shape by analyzing 481 personal ads in a large metropolitan city magazine to determine self‐report characteristics of males and females seeking companionship as well as the desired height, weight, and shape characteristics of the person being sought. Seventy percent of ads specified weight, shape, or height characteristics and of those ads most were heterosexual Caucasian males and females. Male searchers described themselves as tall, fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In general, male and female models featured in advertisements for clothing on Nike's and Under Armour's ecommerce websites mostly upheld notions regarding femininity and masculinity in terms of body norms and concepts related to the body. Most of the female athletes depicted the "thin" ideal Weber and Van Mullem, Representation in Athleisure Images while many of the male athletes depicted the "lean muscular" ideal, body norms that are accepted and valued in society (Andersen et al, 1993;Leit et al, 2002). As was mentioned previously, females and males are susceptible to acquiring eating disorders and body image concerns due to pressure to achieve societal body standards (Law & Labre, 2002;Roberts & Muta, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…In general, male and female models featured in advertisements for clothing on Nike's and Under Armour's ecommerce websites mostly upheld notions regarding femininity and masculinity in terms of body norms and concepts related to the body. Most of the female athletes depicted the "thin" ideal Weber and Van Mullem, Representation in Athleisure Images while many of the male athletes depicted the "lean muscular" ideal, body norms that are accepted and valued in society (Andersen et al, 1993;Leit et al, 2002). As was mentioned previously, females and males are susceptible to acquiring eating disorders and body image concerns due to pressure to achieve societal body standards (Law & Labre, 2002;Roberts & Muta, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…One-third of women's ads "in search of men specified desired physical qualities, among the most frequently cited of which were "fit," "trim," and "muscular" My findings revealed that women, generally believed to be much more concerned with men's financial prospects than their physical attributes, did, in fact, care about appearance. Men were evidently not unaware of these female preferences: Although women were likely to describe themselves as thinner than their actual weight in personal advertisements, men tended to describe their weight as above average (A. E. Andersen, Woodward, Spalder, & Koss, 1993). Women's demands were driven not only by a sense of feminist egalitarianism resulting from the women's movement but also by women's gains in financial independence: As feminist Gloria Steinem wryly observed, attractive women are less likely to date "potbellied men ... thirty years older than they [are] when there is no economic advantage to doing so" (quoted in Agins, 1994, p. Al).…”
Section: No Pecs No Sex1: Men Women and Muscularitymentioning
confidence: 99%
“…Personal advertisements provide a medium for investigating values and gender stereotypes of a heterogeneous nonreactive sample (Gonzales & Meyers, 1993), and they also reflect body shape ideals (Anderson, Woodward, Spalder, & Koss, 1993). Past research on personal ads has found that women more than men offer attractiveness and body weight and look for financial security and physical height, whereas men offer security and request attractiveness and low body weight (Harrison & Saeed, 1977;Koestner & Wheeler, 1988).…”
mentioning
confidence: 99%